Some Properties and Identities of Bernoulli and Euler Polynomials Associated with p-adic Integral on ℤp - D. S. Kim; T. Kim; D. V. Dolgy; S. H. Lee; S.-H. Rim (Abstract and Applied Analysis)
We investigate some properties and identities of Bernoulli and Euler polynomials. Further, we give some formulae on Bernoulli and Euler polynomials by using p-adic integral on ℤp.